Low 2D:4D is associated with delayed age at menarche among women of Sikkim, India - Mondal, Nitish; Rai, Rebaka (Anthropological Review, 2023)
The index-finger and ring-finger ratio (2D:4D) is a potential biomarker that reflects prenatal hormonal exposure and thus has a long-term impact on reproductive health. The present study aims to determine the relationship between the 2D:4D (representing the prenatal hormonal environment, i.e., early androgen exposure) and early or delayed age at menarche among women in Sikkim, India. A total of one hundred nineteen Sherpa tribal women, ages 18–49, from the Soreng district of Sikkim, India, were included in the study using a stratified random sampling method. To calculate the 2D:4D ratio, the lengths of the index and ring fingers (2D and 4D) were measured using standard procedures. The category-wise mean comparison revealed that women with a more feminine 2D:4D ratio (in both left and right hand) had significantly earlier age at menarche (in years) compared to women with a more masculine 2D:4D ratio. The linear regression analysis revealed that the left 2D:4D was significantly related to menarche age. There is an association between the 2D:4D and menarche age, indicating a link between women’s reproduction patterns and the influence of the prenatal hormonal environment as an important factor in attaining an early or delayed menarcheal age.